2015
DOI: 10.1111/acel.12362
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for common pathways in human age‐related diseases

Abstract: Aging is the single largest risk factor for chronic disease. Studies in model organisms have identified conserved pathways that modulate aging rate and the onset and progression of multiple age-related diseases, suggesting that common pathways of aging may influence age-related diseases in humans as well. To determine whether there is genetic evidence supporting the notion of common pathways underlying age-related diseases, we analyzed the genes and pathways found to be associated with five major categories of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 47 publications
5
59
1
Order By: Relevance
“…The aforementioned diseases share underlying molecular processes of aging and other age‐related diseases. This fact agrees with the study of Johnson and colleagues that demonstrates the influence of common anti‐aging pathways in human age‐related diseases . In fact, these ocular pathologies present the nitro‐oxidative damage, mainly at mitochondrial level, as a major cause .…”
Section: Epilogue and Perspectivessupporting
confidence: 92%
“…The aforementioned diseases share underlying molecular processes of aging and other age‐related diseases. This fact agrees with the study of Johnson and colleagues that demonstrates the influence of common anti‐aging pathways in human age‐related diseases . In fact, these ocular pathologies present the nitro‐oxidative damage, mainly at mitochondrial level, as a major cause .…”
Section: Epilogue and Perspectivessupporting
confidence: 92%
“…Interestingly, SNPs located near regulators of senescence and inflammation are particularly associated with diseases of ageing, such as cancer, CVD, and type 2 diabetes, and the strongest association was found with a variant in the CDKN2A gene, which encodes the p16 INK4A protein that is over-expressed in many forms of senescence. These findings were replicated in a meta-analysis that included 410 genome-wide association studies 91,92 . In addition, the variant rs2811712 that is close to the CDKN2A gene was associated with poor physical function in two different cohorts 93 .…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 76%
“…The view that the unhealthy aging trajectory can be traced by investigating patients with the most common ARDs is supported by the consideration that aging is the single largest risk factor for ARD development, and that studies of animal models have identified conserved pathways that modulate both the aging rate and ARD onset (Johnson et al, 2015). …”
Section: Healthy and Unhealthy Aging Trajectoriesmentioning
confidence: 99%